Water quality of rivers that flow into bakun hydroelectric dam reservoir, Sarawak, Malaysia / Teck-Yee Ling, Lee Nyanti and Annestasia Simbut John Masion - Teck-Yee, Ling; Lee, Nyanti; John Masion, Annestasia Simbut (Universiti Teknologi MARA, Pulau Pinang, 2015)
After Bakun Dam was filled to its full supply level 2 years ago, little is known about the water quality of the rivers that flow into the reservoir. After the impoundment, sections of rivers of Batang Balui were submerged. Those rivers are still important for aquatic organisms and they will affect the reservoir water quality. A previous study showed that one of the rivers to the south of the dam has high dissolved oxygen and high turbidity which affected the turbidity in the reservoir. Therefore, the objective of this study was to determine the water quality of some of the other rivers. Results show that all the five rivers are well-aerated with dissolved oxygen of above 7 mg/L. However, the Belepeh River had very high total suspended solids and turbidity when it was raining and it falls in Class III of INWQS. In contrast, turbidity values of the other four rivers complied with Class II standard. In terms of BOD5 when it rained, all the rivers fall in Class III except for the Bulo River which complied with Class II. There is a need to reduce the inflow of sediments into the Belepeh River to provide suitable environment for sensitive aquatic species.